Implementasi Pembelajaran Penguatan Profil Pelajar Pancasila pada Anak Usia Dini di PAUD Terpadu Belia Binuang dan TK Handayani III Penajam - Dahliana, Hasnun; Khojir, Khojir; Muadin, Akhmad (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2023)
This study aims to analyze the planning, implementation, and evaluation of project-based learning to strengthen the profile of Pancasila students in early childhood in North Penajam Paser Utara. The research explores the effectiveness of this approach in addressing learning problems within the context of the Independent Curriculum, which is mandatory for educational units. The qualitative research employed data collection techniques such as observation, interviews, and documentation. Data analysis involved an interactive process of condensing and presenting the data, leading to the formulation of conclusions. The validity of the data was ensured through triangulation of methods and sources. The findings of this study reveal the successful implementation of project-based learning to strengthen the profile of Pancasila students in early childhood at Belia Binuang Integrated PAUD and TK Handayani III in Penajam Paser Utara. The research focused on three key areas: (1) planning P5 learning, which involved formulating objectives, identifying learning content, designing learning activities, and evaluating the learning process; (2) implementing P5 learning, which included thorough preparation, incorporating Pancasila values into every learning activity, collaborating with parents, evaluating and providing feedback, reflecting on the process, and fostering development; and (3) evaluating P5 learning, which employed various assessment methods such as observation, portfolio assessment, formative assessment, role playing, interviews, reflection, and discussion. By examining the planning, implementation, and evaluation stages of project-based learning, this study sheds light on its efficacy in strengthening the profile of Pancasila students in early childhood. These insights contribute to the ongoing efforts to improve early childhood education and inform curriculum development.